Predicting economic activity via Eurozone yield spreads: Impact of credit risk - Matthias Schock (Leibniz Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2015)
A 'lost decade' for the Eurozone is looming on the horizon. Under these circumstances, stable indicators for future economic activity are especially valuable to decision makers. This paper examines the predictive power of the yield spread, one of the most reliable indicators for gross domestic product (GDP) growth. Despite the continuously high level of yield spreads, growth is sparse in the Eurozone. We find this to be caused by default risks, which are distorting the long-term interest rates of many Eurozone countries. Therefore, a new method of risk adjustment is introduced. We employ credit default swap (CDS) spreads on sovereign bonds, which provide a direct measure of credit risk. Incorporating those spreads significantly enhances the in- and out-of-sample predictive power of the yield-spread approach. Ordinary least squares (OLS) and fixed-effects models are used to forecast GDP growth in the Eurozone, and a probit model is used for recession prediction. The results show that the accuracy of predicting growth and recessions using the yield spread is high, provided that biases associated with Eurozone sovereign default risk are considered.
Keywords: G1; E37; E43; E44; 330; yield curve; CDS spreads; economic activity